Investigation of the physicochemical properties and pharmacokinetics of the active compounds in Quercus infectoria gall extract - Roohallah Yousefi (Trends in Pharmaceutical Sciences)
The Quercus genus, known as oak trees, provides important bioactive compounds for pharmaceuticals. Quercus infectoria is recognized for its antimicrobial properties, containing Friedelin, Betulinic Acid, and Gallic Acid. The molecular weight, hydrophobicity, polarity, and solubility of these compounds play a key role in their biological activity and pharmacokinetics, which can be evaluated using SwissADME and PubChem. Lipinski's Rule of Five suggests that optimal molecular weights for oral bioavailability fall between 180 and 500 Da. Assessing the ability of compounds to penetrate the blood-brain barrier is crucial for neurological treatments. Friedelin, a pentacyclic triterpene with antimicrobial and anticancer properties, can penetrate cell membranes due to its hydrophobic nature, but absorption may be limited by its molecular weight. Betulinic acid, a triterpene with antiviral and anticancer properties, is well absorbed. Vanillic acid, a water-soluble phenolic compound, is easily absorbed but liver metabolism may affect its bioavailability. Ellagic acid, a polyphenol with antioxidant and anticancer properties, has complex pharmacokinetics due to conjugate formation and protein interactions. Gallic acid may impact its distribution, while phlorizin is being studied for its potential to inhibit glucosidase in diabetes management. Vescalagin's pharmacokinetics may be influenced by its sugar structure and conjugation sites, and low water solubility could limit its bioavailability. Breaking down Quercus infectoria into smaller compounds could enhance its therapeutic effects. Understanding the physicochemical properties and pharmacokinetics of new drugs and nutraceuticals is essential for evaluating their effectiveness, safety, absorption, and minimizing adverse effects. We study the pharmaceutical properties of Quercus infectoria bioactive compounds.